2022
DOI: 10.3389/fpls.2022.847234
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study Dissects the Genetic Architecture of the Metaxylem Vessel Number in Maize Brace Roots

Abstract: Metaxylem vessels in maize brace roots are key tissue, and their number (MVN) affects plant water and inorganic salt transportation and lodging resistance. Dissecting the genetic basis of MVN in maize brace roots can help guide the genetic improvement of maize drought resistance and lodging resistance during late developmental stages. In this study, we used 508 inbred lines with tropical, subtropical, and temperate backgrounds to analyze the genetic architecture of MVN in maize brace roots. The phenotypic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The plotting script is available online on the webpage https://aozhangchina.github.io/R/LDdecay/LDdecayPlotTool.html . Then, we used the uniform Bonferroni-corrected threshold of α = 1 for the mixed linear model’s significance cutoff as reported in previous studies ( Mao et al., 2015 ; Liu et al., 2022 ). Therefore, the suggested P-value was computed with 1/n (n = 97,862, total markers used), and we obtained a P-value threshold of 1.02×10 -5 for GWAS.…”
Section: Methodsmentioning
confidence: 99%
“…The plotting script is available online on the webpage https://aozhangchina.github.io/R/LDdecay/LDdecayPlotTool.html . Then, we used the uniform Bonferroni-corrected threshold of α = 1 for the mixed linear model’s significance cutoff as reported in previous studies ( Mao et al., 2015 ; Liu et al., 2022 ). Therefore, the suggested P-value was computed with 1/n (n = 97,862, total markers used), and we obtained a P-value threshold of 1.02×10 -5 for GWAS.…”
Section: Methodsmentioning
confidence: 99%
“…With the precise identification of microphenotypic traits, an increasing number of genes that regulate microphenotypes of vasculature, such as the metaxylem vessel number ( KNAT7 , ZmTIP1 ), stele area ( OsNACs , Mei2‐like gene), cortical cell ( bHLH121 ), and stem xylem and phloem traits ( NAC91, ZmTIP1, CLE41/44 , etc. ), are being uncovered, which provides insights for the genetic improvement of crop yield and stress resistance (Barrieu et al ., 1998 ; Li et al ., 2021b ; Liu et al ., 2022 ; Schneider et al ., 2023 ).…”
Section: Applications Of Microphenotypes In Biophysical and Biochemic...mentioning
confidence: 99%
“…Through GWAS, Li Ning [18] successfully identified a gene, ZmFBL4, associated with banded leaf and sheath blight. Numerous studies have successfully identified QTLs related to crucial agronomic traits, thereby showcasing the practicality and efficiency of GWAS [19][20][21][22]. In crops like maize, GWAS has proven invaluable in exploring key genes and identifying potential disease-resistant genes.…”
Section: Introductionmentioning
confidence: 99%